Brittle failure in the parallel-to-grain direction of timber connections with small diameter dowel-type fasteners: A new design model for plug shear. (15th August 2021) - Yurrita, Miguel; Cabrero, José Manuel; Moreno-Zapata, Ezequiel
Highlights: Brittle failure modes may happen in timber connections loaded parallel-to-grain. A new model for brittle failure in joints with small diameter fasteners is proposed. As a design model, it aims to be clear and simple for designers. The new proposal improves the accuracy of the existing models. Abstract: Timber connections with steel dowel-type fasteners may fail in ductile or brittle ways. The design of this joints was traditionally focused on ductile failure, assuming that brittle failure could be avoided by means of geometrical limitations. However, recent studies demonstrated that these assumptions do not always guarantee ductile failure. A new design model for timber connections with small diameter dowel-type fasteners is provided in this paper. Its improved accuracy is demonstrated by analysing an extensive database of experimental tests and comparing its prediction accuracy to that of existing models.